2012
DOI: 10.1105/tpc.111.092304
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Thioredoxin Reductase C Is Localized in Plastids of Photosynthetic and Nonphotosynthetic Tissues and Is Involved in Lateral Root Formation in Arabidopsis

Abstract: Plastids are organelles present in photosynthetic and nonphotosynthetic plant tissues. While it is well known that thioredoxin-dependent redox regulation is essential for leaf chloroplast function, little is known of the redox regulation in plastids of nonphotosynthetic tissues, which cannot use light as a direct source of reducing power. Thus, the question remains whether redox regulation operates in nonphotosynthetic plastid function and how it is integrated with chloroplasts for plant growth. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
72
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 63 publications
5
72
0
1
Order By: Relevance
“…NTRC is exclusive of organisms that perform oxygenic photosynthesis and shows plastid localization in plants (Kirchsteiger et al, 2012). Moreover, biochemical analyses revealed that NTRC is able to conjugate both NTR and Trx activities to efficiently reduce the hydrogen peroxide-scavenging enzyme 2-Cys peroxiredoxin (Moon et al, 2006;Pérez-Ruiz et al, 2006;Alkhalfioui et al, 2007).…”
mentioning
confidence: 99%
“…NTRC is exclusive of organisms that perform oxygenic photosynthesis and shows plastid localization in plants (Kirchsteiger et al, 2012). Moreover, biochemical analyses revealed that NTRC is able to conjugate both NTR and Trx activities to efficiently reduce the hydrogen peroxide-scavenging enzyme 2-Cys peroxiredoxin (Moon et al, 2006;Pérez-Ruiz et al, 2006;Alkhalfioui et al, 2007).…”
mentioning
confidence: 99%
“…Only a few targets were shown to be controlled by NTRC. NTRC functions in the abiotic oxidative stress response (Serrato et al, 2004), starch synthesis (Michalska et al, 2009), Chl synthesis Pérez-Ruiz et al, 2014), the Calvin-Benson cycle (Thormählen et al, 2015), lateral root formation in Arabidopsis (Kirchsteiger et al, 2012), nonphotochemical quenching (Naranjo et al, 2016), as a holdase chaperone function enhancing thermotolerance to Arabidopsis (Chae et al, 2013), and as an electron donor of 2-Cys-peroxiredoxin, thus playing a key role in the detoxification of reactive oxygen species (ROS; Pérez-Ruiz et al, 2006;Spínola et al, 2008;Kirchsteiger et al, 2009). Recent research suggested that cooperative control of chloroplast functions via the ferredoxin-thioredoxin reductase (FTR)/TRX and NTRC pathways is essential for plant viability.…”
mentioning
confidence: 99%
“…Three isoforms of NTR (NTRA, NTRB, and NTRC) are reported in Arabidopsis (Arabidopsis thaliana) that link TRXs to multiple target proteins of metabolic processes. While NTRA and NTRB are dually targeted to cytosol or mitochondria, NTRC is plastid localized and one of the main redox regulators in photosynthetic and nonphotosynthetic active plastids (Serrato et al, 2004;Pérez-Ruiz et al, 2006;Spínola et al, 2008;Kirchsteiger et al, 2009Kirchsteiger et al, , 2012Lepistö et al, 2009;Pulido et al, 2010). NTRC contains a C-terminal TRX domain and acts as a bifunctional enzyme with NTR/TRX activity for the reduction of specific target proteins (Serrato et al, 2004).…”
mentioning
confidence: 99%